2014
DOI: 10.4097/kjae.2014.66.5.392
|View full text |Cite
|
Sign up to set email alerts
|

Anesthetic experience using extracorporeal membrane oxygenation for cesarean section in the patient with peripartum cardiomyopathy: a case report

Abstract: Peripartum cardiomyopathy is a rare form of cardiomyopathy that is associated with significant mortality. It can cause a cardiac arrest during cesarean section even though the patient does not have any previous symptom and sign. The most important thing of anesthesia in this patient is an optimization of hemodynamic and respiratory status. We report the successful general anesthesia using of extracorporeal membrane oxygenation for cesarean section in a 34-year-old woman with fulminant peripartum cardiomyopathy. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 15 publications
(53 reference statements)
0
8
0
Order By: Relevance
“…There have been a few published reports of extracorporeal life support use in pregnant women with PPCM. [23][24][25][26] Only one of the reported patients underwent cesarean section with PCPS support, 26 whereas the remaining patients were treated after delivery. Bouabdallaoui et al reported 10 consecutive patients with PPCM who received veno-arterial-ECMO.…”
Section: Discussionmentioning
confidence: 99%
“…There have been a few published reports of extracorporeal life support use in pregnant women with PPCM. [23][24][25][26] Only one of the reported patients underwent cesarean section with PCPS support, 26 whereas the remaining patients were treated after delivery. Bouabdallaoui et al reported 10 consecutive patients with PPCM who received veno-arterial-ECMO.…”
Section: Discussionmentioning
confidence: 99%
“…One case describes a 34-year-old at term gestation who presented with acutely worsening heart failure and cesarean delivery was performed after full flow ECMO support was established. ECMO was maintained for five days after surgery [14]. In another case an 18-year-old woman developed decompensated heart failure immediately after cesarean delivery and was placed on ECMO as a bridge to recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Anesthesiologists are commonly involved during the delivery phase of those parturients with PPCM by providing anesthesia for cesarean section. Either of general or regional anesthesia have been successfully applied in PPCM in multiple of case reports [16,17]. There is no evidence supporting that general is superior to the neuraxial anesthesia, or vice versa.…”
Section: Discussionmentioning
confidence: 99%